Health-Related Quality of Life and Costs of Posttraumatic Stress Disorder in Adolescents and Young Adults in Germany - Dams, Judith; Rimane, Eline; Steil, Regina; Renneberg, Babette; Rosner, Rita; König, Hans-Helmut (Frontiers in Psychiatry, 2020)
Background: Posttraumatic stress disorder (PTSD) is one of the psychopathological consequences of sexual and/or physical abuse. The economic burden is assumed to be high, whereas health related quality of life and education is negatively affected. This study aims to determine health care costs, health related quality of life, and educational interruption in adolescents and young adults with PTSD after sexual and/or physical abuse in Germany. Methods: This analysis used data of 87 participants aged 14-21 years of a randomized controlled trial. Health care utilization, health related quality of life (EQ-5D-5L), sick leave days, productivity, and delay or failure to achieve educational aims were assessed. Health care costs from a payer perspective were calculated using unit costs for the year 2014. Results: Mean health care costs for a six-month period were 5,243€ (SE 868€). In particular, costs of inpatient stays in psychiatric hospitals, general hospitals and rehabilitation as well as child welfare institutions, were high. In addition, health related quality of life was lower due to anxiety/depression, resulting in a mean EQ-5D index and EQ-VAS score of 0.70 and 61.0, respectively. Furthermore, participants reported on average 27 sick leave days, a productivity loss of 61%, and a delay in education attainment as well as having been unable to achieve educational aims. Conclusion: PTSD in adolescents and young adults is associated with a high economic burden. Health related quality of life was substantially reduced. Furthermore, delay and productivity losses in education were observed. Trial registration: German Clinical Trials Register identifier: DRKS00004787; date of registration: 18th March 2013; https://www.drks.de)